Association between functional performance and return to performance in high-impact sports after lower extremity injury: A systematic review - Vereijken, A.; Aerts, I.; Jetten, J.; Tassignon, B.; Verschueren, J.; Meeusen, R.; van Trijffel, E. (Journal of Sports Science & Medicine, 2020)
After lower extremity injury, only half of the injured athletes return to their pre-injury sports level. Even though functional performance tests are often used to make return to sport decisions, it is unknown whether functional performance is associated with return to performance after such injuries. The aim of this systematic review was to identify, critically appraise, and analyze studies that investigated the association of functional performance tests with return to performance after lower extremity injuries in athletes participating in high-impact sports. MEDLINE, Embase, Web of Science, and CINAHL were systematically searched for relevant studies. Articles were independently screened by two authors and data were obtained from each included study using a data extraction form. Two authors independently scored methodological quality using the Quality In Prognosis Studies tool. A qualitative best evidence synthesis was conducted. Eight studies reported the association of functional performance with return to performance after lower extremity injuries, involving 1,246 athletes after anterior or posterior cruciate ligament reconstruction. No studies were found on the association of functional performance with return to performance for lower extremity injuries other than after anterior or posterior cruciate ligament reconstruction. All included studies had a high risk of bias. Two studies found significant but small associations for selected hop tests after anterior cruciate ligament reconstruction. Low evidence of association between functional performance and return to performance was present after anterior cruciate ligament reconstruction for the triple hop for distance, the 6-meter timed hop, the side hop in female athletes, and for the combination of the single and crossover hop for distance. In athletes after posterior cruciate ligament reconstruction, the vertical jump showed a significant but small association with return to performance. There is no high-quality evidence that functional performance is associated with return to performance after lower extremity injuries in athletes practicing high-impact sports. Low quality evidence suggests small associations after anterior and posterior cruciate ligament reconstruction. No evidence exists for lower extremity injuries other than after anterior or posterior cruciate ligament reconstruction. Therefore, research on functional performance associated with return to performance is recommended in high-quality prospective cohort studies including athletes with any type of lower extremity injury.